Reference Ranges Of Haematological Parameter Concentrations Of Young Adult Males In Khartoum State.: Life Sciences-Medicine - Yaqoob, Mustafa Hussein; Daffa Al, Nisreen; Mohamed, bdalla; Badi, andRehab (International Journal of Life Science and Pharma Research, 2022)
Reference values of haematological parameters such as red blood cells count & haemoglobin (Hb)concentration of Sudanese population is not determined. The aim of this study is to determine the reference ranges of red blood cells count, haemoglobin concentration, haematocrit, MCV, MCH, MCHC and RDW among Sudanese young adult males and compare them to international and regional reference intervals used in practice. This gives an insight towards further setting reference values to Sudanese population in the future. This is a cross sectional study conducted in Khartoum state, Sudan. About 200 male students from three higher educational institutes were selected by a convenient sampling method. The age of study participant was 18 - 25 year. Venous blood samples were collected in EDTAK3 containers for the blood test. RBC’s count, Haemoglobin concentration, Haematocrit, Hb, MCV, RDW were measured for each participant. IBM.SPSS version 21 statistical software was used for data analysis, P< 0.05 was assumed as significant and 95% confidence level was accepted. The results were displayed as mean, standard deviation (SD) and range for each haematological parameter. RBCs 5.29±.41 cell1012/L (4.45 – 6.13), haemoglobin concentration 15.1±1.06 g/dl (12.5 – 17.49), haematocrit 45.94±3.1 % (40.1 – 53.19), MCV 86.92±4.33 fl (77.81 – 95.79), MCH 28.58±1.92 pg (23.72 – 32.29), MCHC 32.9±1.29 g/dl (29.41 – 34.89), RDW-SD 44.86±3.57 fl (38.8 – 52.69) and RDW-CV 13.68±1 % (12 – 15.69). All parameters compared to American ones revealed statistically significant differences. All measured parameters were significantly different from parameters of other African populations. Worldwide used reference intervals are inapplicable in Sudan as haematological parameters showed statistically significant variations.